Setting of an import tolerance for mandipropamid in cocoa beans - Brancato, Alba (EFSA J, 2018)
In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Syngenta Agro GmbH submitted a request to the competent national authority in Austria to set a maximum residue level (MRL) for the active substance mandipropamid in cocoa beans imported from Nigeria and Cameroon. The data submitted in support of the request were found to be sufficient to derive a MRL proposal of 0.06 mg/kg. Adequate analytical methods for enforcement are available to control the residues of mandipropamid on the commodity under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the long‐term intake of residues resulting from the use of mandipropamid according to the reported agricultural practice is unlikely to present a risk to consumer health. The consumer risk assessment is affected by non‐standard uncertainties related to the pending hazard characterisation for the metabolite SYN 500003, which is expected to occur in root crops.